Pengaruh Lokasi dan Citra Merek (Brand Image) terhadap Loyalitas Konsumen di Toko Ar Rahman Karangrejo Tulungagung - Moh. Wahyu Sriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the influence of location variables (X1) and brand image (X2) on consumer loyalty (Y) at the AR Rahman Karangrejo Tulungagung Store. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the research was 93 respondents at the AR Rahman Shop Karangrejo Tulungagung. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y = 3.275 + 0.564 Brand image has a partially significant effect on consumer loyalty, with a sig value. 0.000 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that the location and image of Merel simultaneously and significantly influence consumer loyalty at the AR Rahman Karangrejo Tulungagung Store.